Konkordato mühletinin tasarruflara etkisi - Dağ, İbrahim (My University, 2022)
Tasarruf ve tasarruf yetkisi hem maddi hukukta hem de usul ve takip hukukunda var olan kavramlardır. Bir hakka sahip olan o hak üzerinde dilediği tasarrufu, tasarruf yetkisinin sınırları dahilinde kullanabilir. İcra ve İflas Kanunu’nun 285 ve devamı maddelerinde düzenlenmiş olan konkordato kurumu, mali durumu bozulmuş olan gerçek yahut tüzel kişilerin içinde bulundukları durumu iyileştirmek için hazırladıkları projenin mahkemece tasdik edilmesiyle hüküm ifade eden yeniden yapılandırma prosedürüdür. Konkordato talebi üzerine kanunda aranan şartları sağlayan borçluya ilk olarak geçici mühlet verilir. Geçici mühlet ile başlayıp kesin mühlet ile devam eden süreç boyunca borçlunun, alacaklıların ve hatta üçüncü kişilerin tasarruf yetkileri de konkordatodan etkilenir.Konkordato mühletinin tasarruflara etkisi başlığı altındaki tezimizin ilk bölümündetasarruf ve tasarruf yetkisi kavramlarını, maddi hukuk ile usul ve takip hukuku bakımındaninceleyeceğiz. İkinci bölümde, konkordato ve mühlet kurumlarını tasarruflarla ilişkisidahilinde inceleyeceğiz. Son bölümde ise ilk iki bölümü harmanlayarak konkordatomühletinin tasarruflara etkilerini inceleyerek çalışmamızı noktalayacağız.

Disposition and the power of disposition are concepts that exist both in substantivelaw and in procedural and procedural law. A person who has a right can use any dispositionson that right, within the limits of his power of disposition.The concordat institution, which is regulated in Articles 285 and the following of theExecution and Bankruptcy Law, is a restructuring procedure that takes effect upon the court'sapproval of the project prepared by real or legal persons whose financial situation hasdeteriorated in order to improve their situation. Upon the concordat request, a temporaryrespite is first given to the debtor who meets the conditions sought in the law. During theprocess that starts with a temporary respite and continues with a peremptory respite, thepowers of dispositions of the debtor, creditors and even third parties are also affected by theconcordat. In the first part of our thesis under the title of the effect of the concordat respite onthe dispositions, we will examine the concepts of disposition and power of disposition interms of substantive law, procedural and procedural law. In the second part, we will examinethe concordat and respite institutions in relation to dispositions. In the last part, we willconclude our work by blending the first two parts and examining the effects of the concordatrespite on dispositions.
The effect of the concordat respite on dispositions
Keywords: Bankruptcy; Composition (Law); Concordat; Concordat Respite; İflas; Konkordato; Konkordato (Hukuk); Konkordato Mühleti Disposition; Power of Disposition; Tasarruf; Tasarruf Yetkisi; Turkey; Türkiye